Cell cycle-dependent association of HSP70 with specific cellular proteins (The Rockefeller University Press, 1989)
In asynchronous populations of HeLa cells maintained at control or heat shock temperatures, HSP70 levels and its subcellular distribution exhibit substantial heterogeneity as demonstrated by indirect immunofluorescence with HSP70-specific monoclonal antibodies. Of particular interest is a subpopulation of cells in which the characteristic nuclear accumulation and nucleolar association of HSP70 is not detected after heat shock treatment. This apparent variation in the heat shock response is not observed when synchronized cells are examined. In this study, we demonstrate that three monoclonal antibodies to HSP70, in particular, do not detect nucleolar-localized HSP70 in heat-shocked G2 cells. This is not due to an inability of G2 cells to respond to heat shock as measured by increased HSP70 mRNA and protein synthesis, or due to a lack of accumulation of HSP70 after heat shock in G2. Rather the epitopes recognized by the various antibodies appear to be inaccessible, perhaps due to the association of HSP70 with other proteins. Non-denaturing immunoprecipitations with these HSP70- specific antibodies suggest that HSP70 may interact with other cellular proteins in a cell cycle-dependent manner.